Optimizing fluconazole dosing in acute renal failure patients undergoing continuous renal replacement therapy: A population pharmacokinetic/pharmacodynamic study - Zhang, Shengnan; Zhang, Wenhua; Wu, Tingting; Qin, Yuanfang; Pei, Qi (Frontiers in Pharmacology, 2025)
Fluconazole pharmacokinetics in acute renal failure (ARF) patients undergoing continuous renal replacement therapy (CRRT) are significantly influenced by the combined effects of impaired renal function and CRRT, yet current dosing guidelines do not account for these complexities, leading to suboptimal therapy and treatment failure. This study aimed to address these limitations by developing a population pharmacokinetic model for fluconazole in ARF patients receiving CRRT, evaluating guideline-recommended dosing regimens for pharmacokinetic/pharmacodynamic target attainment, and then developing software to optimize fluconazole dosing in complex clinical CRRT scenarios. A total of 297 literature-sourced plasma concentration data points from 15 ARF patients and one patient with normal renal function, all receiving CRRT, were used for model construction. The treatment target was set as the 24-h area under the free drug concentration-time curve to the minimum inhibitory concentration ratio ≥100. The web application was developed using R and R packages. The final pharmacokinetic model comprised a central and CRRT compartment, with renal failure and CRRT doses influencing clearance and body weight affecting central compartment distribution volume. Simulations revealed that the guideline-recommended loading (800 mg or 12 mg/kg QD) and maintenance doses (400 mg or 6 mg/kg QD) achieved limited target attainment at low CRRT doses and failed at moderate to high CRRT doses. Consequently, dose adjustments based on body weight and CRRT parameters are recommended. A user-friendly, visual, and interactive Shiny application was developed to assist clinicians in optimizing fluconazole dosing in this challenging patient population.